RELIGIOUS MODERATION ON PTKIN'S GEN Z PERSPECTIVE - Amalia Irfani; Azkiya Ramadani (UIN Sunan Kalijaga Yogyakarta, 2026)
Religious moderation has become a strategic issue in recent years, eliciting diverse views, particularly among the younger generation. Gen Z, as a group growing up in the digital and globalized era, faces significant challenges in maintaining tolerance, managing differences, and developing an inclusive attitude amidst cultural and religious diversity. This research examines how students, particularly at IAIN Pontianak, a self-proclaimed Islamic university pioneering religious moderation, understand and internalize the concept of moderation in their daily lives. The research methodology employed a qualitative social situation approach, involving observation, interviews, and the distribution of an online questionnaire via Google Form. Analysis focused on students' daily interactions and behaviors as a reflection of their understanding of religious moderation. The theoretical foundation of this research refers to the principles of religious moderation, which emphasize tawasuth (the middle path), tasamuh (tolerance), deliberation, and national commitment as strategies to counter both extremism and excessive liberalism. The results indicate that students generally have a moderate attitude in responding to socio-religious change. They are less prone to negative stigma when faced with cultural and religious differences and are able to display an inclusive attitude in daily interactions. These findings confirm that religious moderation is a crucial asset for Gen Z to continue the nation's struggle with a spirit of tolerance, respect for diversity, and a strong commitment to nationalism. Keywords: Gen Z Perspective, PTKIN, Religious Moderation Moderasi beragama telah menjadi isu strategis dalam beberapa tahun terakhir, memunculkan beragam pandangan, khususnya di kalangan generasi muda. Generasi Z, sebagai kelompok yang tumbuh di era digital dan globalisasi, menghadapi tantangan signifikan dalam menjaga toleransi, mengelola perbedaan, dan mengembangkan sikap inklusif di tengah keragaman budaya dan agama. Penelitian ini mengkaji bagaimana mahasiswa, khususnya di IAIN Pontianak, sebuah universitas Islam yang memproklamirkan diri sebagai pelopor moderasi beragama, memahami dan menginternalisasi konsep moderasi dalam kehidupan sehari-hari mereka. Metodologi penelitian menggunakan pendekatan situasi sosial kualitatif, yang melibatkan observasi, wawancara, dan penyebaran kuesioner daring melalui Google Form. Analisis difokuskan pada interaksi dan perilaku sehari-hari mahasiswa sebagai refleksi pemahaman mereka tentang moderasi beragama. Landasan teoritis penelitian ini mengacu pada prinsip-prinsip moderasi beragama, yang menekankan tawasut (jalan tengah), tasamuh (toleransi), musyawarah, dan komitmen nasional sebagai strategi untuk melawan ekstremisme dan liberalisme yang berlebihan. Hasil penelitian menunjukkan bahwa mahasiswa umumnya memiliki sikap moderat dalam menanggapi perubahan sosial-agama. Mereka cenderung kurang terpengaruh oleh stigma negatif ketika berhadapan dengan perbedaan budaya dan agama, serta mampu menunjukkan sikap inklusif dalam interaksi sehari-hari. Temuan ini menegaskan bahwa moderasi beragama merupakan aset penting bagi Generasi Z untuk melanjutkan perjuangan bangsa dengan semangat toleransi, menghormati keberagaman, dan komitmen yang kuat terhadap nasionalisme. Keywords: Gen Z Perspective, PTKIN, Religious Moderation